Unveiling the antimicrobial and biocontrol potential of the Ascomycete fungus, Clonostachys rosea: A review - Gowrisri Nagaraj; Elango Kolanthasamy (The Microbe, 2025)
Clonostachys rosea, originally named Gliocladium roseum, was reclassified in 1999 due to significant differences in morphology, ecology, teleomorph, and DNA sequences. Belonging to the Ascomycota phylum, it exhibits a global distribution with isolates found in soil, plant roots, and various hosts, including barley, onion, and cocoa. Known for its biocontrol capabilities, C. rosea effectively colonizes plants and pests, reducing damage from Thrips tabaci and Botrytis cinerea among others. Morphologically, it produces conidia and chlamydospores, adapting to adverse conditions. Genomic studies reveal a complex genetic makeup with numerous genes related to biocontrol mechanisms. Its biocontrol efficacy is attributed to mechanisms like mycoparasitism, competition for nutrients, and induced systemic resistance (ISR). Additionally, C. rosea produces enzymes and antibiotic compounds that degrade fungal cell walls and inhibit pathogen growth. Studies highlight its potential against various plant pathogens, nematodes, and even insects, making it a versatile agent in agriculture. Its endophytic behavior and ability to induce plant defense responses further enhance its utility in sustainable pest and disease management. Overall, the diverse biocontrol tactics and adaptability of C. rosea highlight its potential as a cutting-edge, environmentally responsible tool to promote sustainable agriculture and call for more research in contemporary pest management techniques.